Indigenous environmental knowledge and challenging dualisms in development: observations from the Kalahari. Issue 3 (3rd April 2018) - Dyll, Lauren
ABSTRACT: The dividing practice of separating indigenous and scientific knowledge should be avoided. The article illustrates how these forms of knowledge are negotiated in development projects where research participants are included as co-researchers. Data were collected through interviews and participant observation during fieldtrips to the Kalahari. !Xaus Lodge, the first research site, a poverty alleviation tourism asset built by the South African government and owned by the ǂKhomani and Mier communities. The second research site was Biejse Poort, where an intercultural rock engraving recording project was conducted. The article discusses challenging dualisms that are usually evident in development projects.